Canine congenital portosystemic shunts: Disconnections dissected. (May 2016) - Van den Bossche, L.; van Steenbeek, F.G.
Highlights: The clinical signs, diagnostics and histological abnormalities of canine congenital portosystemic shunts are reviewed. Available treatments and prognosis are discussed. Aetiology and physiology of both extrahepatic and intrahepatic subtypes are addressed. Abstract: Canine congenital portosystemic shunts (CPSS) are vascular anomalies that connect the portal vein with the systemic circulation, therefore bypassing the hepatic parenchyma. Portosystemic shunts exist in two different subtypes: extrahepatic and intrahepatic. This congenital disorder is also described in mice, cat, sheep and man. Research has been focused on pathophysiology, diagnostics and treatment of CPSS and this has resulted in increased knowledge, although the aetiology of the disease remains unclear. This review focuses on the aetiology and genetic basis of both intra- and extrahepatic shunts.